INTRERPRETASI SENSE OF PLACE DALAM GAME CALL OF DUTY 4: MODERN WARFARE - Pundra Rengga Andhita (Jurnal El-Hamra : Kependidikan dan Kemasyarakatan, 2019)
Sense of Place is related to emotional relationships born from the interaction between humans and places. The game was born as a public space involving the interpretation of the owner of the place, views or perceptions of reality outside the game. Call of Duty 4: Modern Warfare shows the existence of coherent elements of place including physical settings, images and meanings of the game. This research shows that physical settings in the game Call of Duty 4: Modern Warfare have strong relevance between images in real-life games outside the game. Relevance is arranged with excellent detail so that it makes players easier to assemble imaginations that are identical to everyday life. The aspects of the image generated in the game Call of Duty 4: Modern Warfare are arranged very precisely through a combination of visual appearance and strong narration. The interpretation order in this game is inseparable from the existence of games as one of the ideal communication channels to disseminate ideas according to the sender. The meaning formed through this game is an accumulation of physical settings and adequate narration according to the will of the maker. These three things succeeded in shaping players' perceptions in the direction expected by producers of Call of Duty 4: Modern Warfare.Key Words: call of duty, sense of place, video, games, public space,